Improving environmental performance with implementation of enviromental management system - Ho, Lee Lee. (Universiti Malaysia Sarawak (UNIMAS), 2011)
The Environmental Management System (EMS) structure recognizes that both envionmentL nd economic performances are directly linked with each other. The pimary objective of implementing EMS is to continously improve an organization's enviromental perfomance. Benefits of succesful implementation of an EMS include cost reduction in pollution prevention activities, compliance with legislation requirements, and a better organizational image internationally and locally. This research looks into 4 most common framewoks of EMS; 1) ISO 14001, 2 ) USEPA's Performance track, 3) Responsible Care R, and 4) Eco management Audit Scheme.